Identifying the factors that affect the willingness of pig farmers to participate in the electronic prescription system - SUGINO, Hiroaki; ENDO, Yuko; FUJIMOTO, Kyoko; YOKOYAMA, Takashi; SATO, Takeshi; HAGA, Takeshi; KAWAMURA, Nozomi; SUGIURA, Katsuaki (Journal of Veterinary Medical Science, 2022)
Electronic data collection systems are being developed in countries around the world to monitor antimicrobial use at farm level. We conducted a questionnaire survey that is destined for pig farmers who are then able to communicate what factors influence their willingness to participate in an electronic prescription system. A principal component analysis was performed on the variables that were associated with the willingness to participate in the system. Using the principal components obtained from the principal component analysis and the attributes of the farmers as explanatory variables, we performed a logistic regression analysis. The results revealed that farmers with a high level of information technology (IT) literacy and a certain degree of active business management and farmers who are not currently familiar with business management practices but who are willing to use data were more willing to participate in the electronic prescription system than those who do not have a high level of IT literacy and/or who are not willing to use data for business management. Contrarily, farmers’ intention to manage drug usage does not contribute to the willingness to participate in the system. These results show that the farmers’ understanding of the benefits and ease of participation in the electronic prescription system is important for establishing the system, thus promoting the convenience of the system is the most effective way to gain cooperation of farmers when establishing the system.